PENENTUAN UKURAN NANOPARTIKEL ZnO SECARA SPEKTROSKOPIK - Yayah Yuliah; Sri Suryaningsih (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
At the nano scale the material properties depend on the size such that the characteristics of the materials can be engineered by controlling its size. Determining of the nano-particles size cannot be carried out easily because no available measuring instruments with accuracy in the order of nano which can be used directly. Electron microscope (TEM), which is considered as the most reliable tool in determining the size at the nano-scale is also not easy to accomplish. Indirect measurement method utilizing various spectrometers such as XRD, UV-Vis, and PL can be exploited to overcome this obstacle. In this study, the nano particles size was determined by analyzing the UV-Vis absorption spectra of materials via the effective mass model at the wavelength of the edge and the peak spectra’s. TEM Photos were used for confirmation. Three ZnO nano particles synthesized chemically used as the analyzed samples. Average particle size of each 4,92nm, 4.66 nm and 5,57nm were resulted by using the λedge of UV-Vis spectra’s whereas from the λpeak extracted 9.83 nm, 9,32nm and 11.3 nm of particles size respectively. TEM photograph show 7.2 nm, 6.31 nm and 26.37 nm average particle sizes for each ZnO sample. The results commonly are in the same order and particularly have similar trend. The overall results showed that the determination of nano particles size spectroscopycally make available informative results as an initial study.Keywords: nano size, spectroscopy, effective mass model.